Overcoming Sleep Problems in Senior College Students with Hypnotherapy: A Trial - Umi Nur Kholifah Dinata; Konto Iskandar Dinata (unprimdn.ac.id, 2023)
This study aims to determine the effectiveness of hypnotherapy in reducing insomnia scores in final year students. This study uses a quasi-experimental single design method and one group pretest experimental design, posttest design, namely the research design used to influence an effect (intervention) in a single case. The methods that used data collection are in the form of observation, unstructured interviews, and measurements through the Pittsburgh Rating Insomnia Scale. The collection of assessment data refers to the author. These results indicate that there is a difference in the level of insomnia between before and after a visual hypnotherapy intervention. From the existing insomnia rate scores, the results show a decrease in the pre, post, and follow-up scores on the insomnia rates seen by the subjects.